2009
DOI: 10.1093/ejo/cjn125
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of malocclusion and its relationship with socio-demographic factors, dental caries, and oral hygiene in 12- to 14-year-old Tanzanian schoolchildren

Abstract: The aim of this study was to assess the prevalence of malocclusion and its association with socio-demographic characteristics, caries experience, and level of oral hygiene in 12- to 14-year-old schoolchildren residing in two socio-economically different districts of Tanzania. A total of 1601 children (mean age 13 years, 60.5 per cent girls) attending 16 primary schools in Kinondoni and Temeke districts participated in a clinical examination and were interviewed in school settings. Chi-square and multiple logis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
207
6
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(244 citation statements)
references
References 36 publications
24
207
6
7
Order By: Relevance
“…In summary, this typology classifies census districts into area types based on a scale of median income. In line with our study, Mtaya et al 24 classified two districts of Tanzania by differences in employment and literacy rates, and proportions of the population using electricity. At the same time, higher levels of mother's education, which was the socioeconomic variable used at the individual level in the present study, had a protective effect on their children's occlusion.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In summary, this typology classifies census districts into area types based on a scale of median income. In line with our study, Mtaya et al 24 classified two districts of Tanzania by differences in employment and literacy rates, and proportions of the population using electricity. At the same time, higher levels of mother's education, which was the socioeconomic variable used at the individual level in the present study, had a protective effect on their children's occlusion.…”
Section: Discussionsupporting
confidence: 88%
“…8,24 Whenever associations between socioeconomic variables and malocclusions are reported, these could reflect differential access to orthodontic treatment. In the United States, for example, orthodontic treatment was more frequent in higher income groups, according to the third National Health and Nutrition Examination Survey, 25 showing greater uptake of treatment in groups with a higher socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of articles analyzed data from African populations: Tanzania [13][14][15], Nigeria [10][11][12], Sudan [16], Senegal [17], and Keny [18]. Four articles looked a at populations from Southeast Asia, including China [4,5], Malaysia [7], and Singapore [8].…”
Section: Resultsmentioning
confidence: 99%
“…For example, several studies have indicated that Asian races have a higher prevalence of Angle class III malocclusion than other races [4][5][6][7][8][9][10]. In some instances population data have shown conflicting reports, such as differing studies among Nigerian children reporting Angle class III malocclusion prevalence ranging from 1.2% (1993) up to 11.8% (2004) [11][12][13].…”
Section: Introductionmentioning
confidence: 99%